Comparing intentional vocabulary learning strategies of rote-copying vs read-plus - Wong, Sze Wei, 1987-; Anie Attan, supervisor; Fakulti Pendidikan (2013)
Thesis (Sarjana Pendidikan (Pengajaran Bahasa Inggeris sebagai Bahasa Kedua)) - Universiti Teknologi Malaysia, 2013